PERANAN ATRAKSI WISATA BUDAYA DI DESA KERTALANGU - Muhammad Akzar; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2013)
Abstract This research is motivated by the role and function of ecotourism in balancing tourism. Located on the outskirts of the city, village Kertalangu felt threatened by various developments over the land. In maintaining wetland village then made a cultural attraction called Desa Budaya Kertalangu. This study attempts to discuss the role of cultural tourism attractions in ecotourism, which is based on cultural preservation, community development and local economic development. In general, the implementation of the research uses the principles of ecotourism are associated with the current conditions that exist in the village Kertalangu. The processed data is sourced from primary and secondary data through: interviews, observation and documentation. Then the data is described and analyzed based on the concept of ecotourism is descriptive qualitative. Based on this research, the role of the community in the management of the attraction of Tourism on increasing the level of the economy is still less than optimal. The existence of several barriers such as the farmers in the world of character education and the obligation Balinese Hindus in worship. But the one hand, this village is able to preserve the natural environment. The village and investors managed to create sustainability of the rice fields of urban planning threat.